Effective Strategies for Developing Writing and Reading Skills of Young Kids (Eurasian Journal of Learning and Academic Teaching, 2022)
All primary school students have the same objective of becoming proficient readers. For English language learners, this task is particularly difficult, particularly in the area of writing. Because of how text-oriented the world has become; writing has been regarded as one of the most important abilities. Due to this transition, both ESOL instructors and teachers in the mainstream are in great need of efficient methods to help this particular population's writing skills. The goal of this initiative is to offer evidence-based strategies for enhancing ESL students' writing abilities. The results imply that this objective can be achieved through the use of technology, pre-taught vocabulary, different teacher influences, and the adoption of beneficial diversified literacy practices